2011
DOI: 10.1016/j.pbb.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the galanin gene show decreased sensitivity to nicotine conditioned place preference

Abstract: Previous work has indicated that the neuropeptide galanin decreases sensitivity to the rewarding effects of morphine and cocaine, but increases alcohol drinking. The aim of the current study was to examine the role of galanin signaling in nicotine reward by testing the effects of nicotine in mice lacking galanin peptide (Gal −/−) as compared to wild-type (Gal +/+) controls. Using an unbiased, three-chamber conditioned place preference (CPP) paradigm the dose-response function for nicotine CPP was tested in Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…Galanin is reported to have an inhibitory effect on dopamine release in rat striatal slices (Tsuda et al, 1998), a finding that supports the ability of galnon to attenuate rewarding effects of drugs of abuse. Interestingly, a recent study found that Gal À/À mice are less sensitive to the rewarding effects of nicotine, as higher nicotine doses were required to produce a significant CPP in these mice compared with + / + counterparts (Neugebaur et al, 2011). This finding is the opposite of what would be expected, given our current results.…”
Section: Figurecontrasting
confidence: 84%
“…Galanin is reported to have an inhibitory effect on dopamine release in rat striatal slices (Tsuda et al, 1998), a finding that supports the ability of galnon to attenuate rewarding effects of drugs of abuse. Interestingly, a recent study found that Gal À/À mice are less sensitive to the rewarding effects of nicotine, as higher nicotine doses were required to produce a significant CPP in these mice compared with + / + counterparts (Neugebaur et al, 2011). This finding is the opposite of what would be expected, given our current results.…”
Section: Figurecontrasting
confidence: 84%
“…Reduced mechanical allodynia after nerve injury (Kerr et al, 2000a;Holmes et al, 2003) (Mazarati et al, 2000) Marked reduction in levels of prolactin in the anterior pituitary and in plasma (Wynick et al, 1998) Decreased severity of cerulein-induced acute pancreatitis (Bhandari et al, 2010b) Reduced insulin secretion in response to non-neuronal stimulation and impaired glucose elimination (Ahren et al, 2004) Decreased food consumption on high-fat diet (Adams et al, 2008;Karatayev et al, 2010) Decreased ethanol intake and preference in female mice. Decreased orexin and melanin-concentrating hormone in the perifornical lateral hypothalamus (Karatayev et al, 2010) Increase in opiate withdrawal behavior (Zachariou et al, 2003) Decreased sensitivity to nicotine and no increase in ERK2 activation in mice that showed nicotine conditioned place preference (increase in WT) (Neugebauer et al, 2011) Increase in secreting sweat glands following thermal stimulation (Vilches et al, 2012) GAL 1 (Jacoby et al, 2002)/C57BL/6J and 129T2/SvEmsJ Increased sensitivity to both heat and cold intact. Increased duration of pain-like behavior after nerve injury (Blakeman et al, 2003) No difference in mechanical or thermal thresholds in intact animals but increased hyperalgesia after thermal injury and faster recovery after spinal nerve ligation (Malkmus et al, 2005) No difference in regeneration in vivo (Blakeman et al, 2003) or in vivo (Blakeman et al, 2003;Mahoney et al, 2003a) Increase in opiate withdrawal behavior Spontaneous seizures and reduced plasma levels of IGF-1.…”
Section: Galanin Genes and Peptides-genomicmentioning
confidence: 99%
“…For example, galanin-KO mice have reduced sensitivity to nicotine reward, and galanin-mediated signaling via GAL 1 blocks nicotine reward (Jackson et al, 2011;Neugebauer et al, 2011).…”
Section: Galanin Family Peptides and Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Galanin, acting through its receptor subtypes, has been shown in rodent models to modulate reward and withdrawal responses from drugs of abuse (Hawes et al, 2008;Zachariou et al, 1999). Of relevance to nicotine dependence, mice lacking the galanin peptide display decreased sensitivity to nicotine reward (Neugebauer et al, 2011). Further, galanin, mediated via GALR1, blocks nicotine reward and reverses physical nicotine withdrawal signs (Jackson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%